2020
DOI: 10.1080/1331677x.2019.1700386
|View full text |Cite
|
Sign up to set email alerts
|

Is there a common path for the integration of European Union banking systems?

Abstract: The main objective of this research article is to explore hypothesis about the integration of the banking systems in European Union (EU). Increasing the European Union member states degree of convergence and integration is one of the major challenges faced by the European Economic and Monetary Union (EMU). The empirical analysis is based on the non-linear time-varying coefficients factor model designed by Phillips and Sul for the sample period 2007-2017. Our results indicate the rejection of the convergence hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Despite the fact that there is no doubt that fiscal policy can influence economic choices, it is by no means obvious, on an ex ante basis, that the reduction of tax rates will eventually lead to a wider and more efficient economy (Gale and Samwick, 2014). Moreover, Spulbar et al (2020a) suggested that integration and economic convergence represent fundamental elements in the structure of the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that there is no doubt that fiscal policy can influence economic choices, it is by no means obvious, on an ex ante basis, that the reduction of tax rates will eventually lead to a wider and more efficient economy (Gale and Samwick, 2014). Moreover, Spulbar et al (2020a) suggested that integration and economic convergence represent fundamental elements in the structure of the European Union.…”
Section: Introductionmentioning
confidence: 99%